CEDERA AKIBAT KECELAKAAN LALU LINTAS DI KOTA MANADO - Kristanto, Erwin; Mallo, Johannis; Yudhistira, Aria (UNIVERSITAS SAM RATULANGI, 2009)
Abstract: Nowadays, the incidence of traffic accidents increases annually. Injuries caused by traffic accidents show specific patterns, which differ from that of injuries due to other causes. Information of injury patterns due to accidents can be very useful in the management of treatment. The aim of this retrospective study is to describe the kinds of injuries in autopsied victims due to traffic accidents, which were autopsied, and in some cases handled in Prof.dr.R.D.Kandou Manado General Hospital from 2004 until 2008. The results showed that 77.7% of deaths were due to traffic accident head injuries, and 22.2% to chest injuries. We observed that they had obvious internal organ damage, especially in the abdomen, which observation could not have been predicted just from external examination. Therefore, it can be concluded that not only deaths by traffic accidents, but all fatalities should undergo autopsy to verify the exact cause of death. Keywords: injury pattern, retrospective study, forensic autopsy Abstrak: Angka kecelakaan lalu lintas tiap tahun meningkat. Cedera yang ditimbulkan memiliki pola tertentu yang berbeda dengan cedera akibat kekerasan lain. Informasi mengenai pola cedera pada kecelakaan lalu lintas dapat digunakan dalam pengobatan. Studi retrospektif ini mendeskripsi-kan cedera yang ditemukan pada autopsi korban kecelakaan lalu lintas di rumah sakit umum Prof.dr.R.D Kandou di Manado, periode tahun 2004 – 2008. Hasil survei menemukan bahwa 77,7% kasus kematian akibat kecelakaan lalu lintas disebabkan oleh cedera kepala, dan 22,2 % akibat cedera pada dada. Dari pengamatan penulis tampak dengan jelas kerusakan organ dalam, terutama pada perut tidak dapat diperkirakan hanya dengan pemeriksaan luar mayat. Perlu dipikirkan bersama agar dapat diciptakan kondisi di mana korban meninggal pada kasus kecelakaan lalu lintas maupun untuk kasus yang lain dapat menerima pelayanan autopsi forensik. Kata kunci: Pola cedera, studi retrospektif, autopsi forensik